Ondori crochet lace with complete diagrams - Aoyama, Chizuko; Kawahara, Koichiro; Iida, Katsuhiko (Ondorisha Pub., 1977)
Originally collected by Gilbert E. Witte for his collection called the Tennyson Library of Crochet ; collection begun with pieces from Flora Emily Tennyson & Flora Dell Stout and added to with material from Betty Clausen, Mildred Brown, Claudette Firlit, Doreen Hope Noonan, Marie Wamhoff, Norma P. Greene, Jane Hansen, Jean Stivers, and Sheila Fahy